Alternative Co-Teaching in Practical Lesson to Teach Speaking at SMK-SMTI Pontianak - Marwandi Marwandi; Yohanes Gatot Sutapa Y; Urai Salam (International Journal of Learning and Instruction (IJLI), 2019)
This paper was a classroom action research aiming at answering and finding out on how the implementation and how teachers’ collaboration through alternative co-teaching improved the students’ speaking in grammar, pronunciation, fluency, and process explanation at Vocational High School (SMK) SMTI Pontianak. This study involved 28 students from Year – 11 students of academic year 2016/2017. The data were collected through observation, field note, questionnaire and test. The result indicated that the use of microphone and speaker were needed to avoid noise level in the workshop and keep the quality of the students’ speaking tests better and clear. The productive teacher used bilingual during briefing; especially technical words related to parts of the machine, personal protective equipment, and process of making a product. The students were able to describe the machine used including parts and its functions, personal protective equipment, and process of making a product based on the job sheet given by the productive teacher. Alternative co-teaching in practical lesson also helped the students to describe process fluently, accurately, and grammatically. Moreover, the students have more time to practice English orally in practical lesson where the teaching hour is three times longer than the regular English classroom.